Towards an extensive exploitation of solar PV technology in Libya: Legislative, economic and environmental considerations - A. Almaktar, M (Libyan Journal of Science &Technology, 2022)
This paper investigates the issue of investment in renewable energy (RE) particularly solar photovoltaic (PV) as an electricity supplier and discusses the most important factors which affect the promotion and expansion of PV systems. The paper firstly provides a general overview of Libyan conventional fuel resources, its electrical energy status, and solar energy potential in the country. In addition, most important international experiences on Feed-in Tariff (FiT) policy are reviewed. The Libyan electricity tariff compared to the international electricity tariffs is also discussed. Furthermore, economic and environmental results of a small PV system installed in Benghazi is analyzed using the Hybrid Optimization Model of Energy Resources (HOMER) software. The simulation study considers different scenarios and rates of FiT, interest rate, and electricity tariffs. Results show that the FiT can play a vital role in developing a knowledge-based economy and encouraging the public to use such a clean energy source thus increasing the share of renewable energies in the total national energy mix. The findings of the paper are very important for all key players including the Libyan government, decision-makers, the national grid utility operator, industries, the PV system investor, and the environment.